Research of the impact of the method of heating of heat units on the qualitative characteristics of treated materials - Nikolsky, Valeriy; Нікольський, Валерій; Oliynyk, Olga; Олійник, Ольга; Pugach, Andrii; Пугач, Андрій Миколайович; Alieksandrov, Oleksandr; Александров, Олександр; Gnatko, Olena; Гнатко, Олена; Chernetskyi, Yevhenii; Чернецький, Євгеній (ПП «ТЕХНОЛОГІЧНИЙ ЦЕНТР», Український державний університет залізничного транспорту, 2018)
An analytical method for calculating the chemical potentials of the components of the gas-solid system based on thermodynamic calculations of carbon potentials of the С–О–Н–N gas mixture (combustion products of the methane-air mixture) and the solid phase (alloyed steel) is developed. Dependences describing the influence of the main parameters of heating the medium composition, flow rate, as well as their interaction, on metal losses associated with decarburization are obtained. Thermodynamic calculations of carbon potentials of alloyed steel and natural gas combustion products of different composition (α=0.2÷1.2), metal and combustion products temperatures of 1,100÷1,500 K are performed. Based on the analysis of the structure of the thermal and diffusion boundary layers, it is proved that the decrease in the temperature of the layer of combustion product flowing around the solid product and surface flow rate reduces the diffusion flow of carbon in the boundary layer. This effect reduces the decarburization of steel. It is found that when heating the heat unit according to the principle of indirect radiant heating (IRH) during the operation of the flat-flame burner, the main gas volume, localized at the metal surface, has a temperature significantly lower than the layer adjacent to the lining. This reduces the metal loss with decarburization compared with furnaces of the traditional heating system. Combustion of gas in flat-flame burners with an intense circulation of combustion products in the working space of the heat unit ensures that the heated products have a uniform composition of combustion products corresponding to a practically equilibrium one. This allows recommending flat-flame burners for widespread use in modern heat-power units in the industry. Розроблено аналітичний спосіб розрахун-ку хімічних потенціалів компонентів в системі газ-тверде, заснований на термодинамічних роз-рахунках вуглецевих потенціалів газової сумі-ші С–О–Н–N (продуктів згоряння метано-пові-тряної суміші) і твердої фази (легованої сталі). Отримано розрахункові залежності описують вплив основних параметрів нагріву складу сере-довища, швидкості обтікання, а також взаємо-дію на втрати металу, пов'язані з обзневуглецю-ванням. Виконано термодинамічні розрахунки вугле-цевих потенціалів легованої сталі і продуктів згоряння природного газу різного компонентного складу (α=0,2÷1,2), температур металу і продук-тів згоряння 1100÷1500 K.На основі аналізу структури теплового і дифузійного приграничних шарів доведено, що зменшення температури шару продуктів згорян-ня, що омиває тверде виріб, і швидкості обтікан-ня поверхні зменшує дифузний потік вуглецю в приграничному шарі. Даний ефект сприяє зни-женню зневуглецювання сталі.Встановлено, що при обігріві теплоагрегату за принципом непрямого радіаційного обігріву (НРО) при роботі плоскополум'яного пальника, основний газовий обсяг, локалізований у поверхні металу, має температуру істотно меншу, ніж шар, прилеглий до кладки. Це зменшує втрати металу з зневуглецюванням в порівнянні з печами традиційної системи обігрівуСпалювання газу в плоскополум'яних пальни-ках при інтенсивній циркуляції продуктів зго-ряння всередині робочого простору теплоагрега-ту забезпечує оброблюваних виробів однорідний склад продуктів згоряння, що є відповідним прак-тично до рівноважного. Це дозволяє рекомен-дувати плоскополум'яні пальники до широкого застосування в сучасних енерготехнологічних апаратах в промисловості.
Дослідження впливу способу нагріву теплових агрегатів на якісні характеристики матеріалів, що обробляються
Keywords: heat-treatment furnace; термообробна піч; boundary layer; прикордонний шар; decarburization; зневуглецювання; flat-flame burner; плоскополум'яний пальник; temperature control; контроль температури